Encyclopedia of human geography - Warf, Barney 1956-.; SAGE Knowledge (Online service). (Thousand Oaks, Calif. London SAGE, 2006)
Human geography has undergone a conceptual and methodological renaissance that has transformed the field into one of the most dynamic social sciences. This encyclopedia, on this relatively new strand of geography, considers the new developments in the field.
"A SAGE reference publication."
Includes bibliographical references and index.
Keywords: Human geography -- Encyclopedias; Electronic books